Identification of Stroke and TIA in Patients With Acute Dizziness, Vertigo or Imbalance in Emergency Departments of Primary Care Hospitals: Early Experiences With a Network-Based Telemedical Approach - Müller-Barna, Peter; Leinweber, Christina; Pfaffenrath, Julia; Schütt-Becker, Nina; von Martial, Rascha; Greck, Susanne; Hubert, Nikolai; Rambold, Holger; Haberl, Roman; Hubert, Gordian Jan (Frontiers in Neurology, 2022)
Background: Acute dizziness, vertigo and imbalance are frequent and difficult to interpret symptoms in the emergency department (ED). Primary care hospitals often lack the expertise to identify stroke or TIA as underlying causes. A telemedical approach based on telestroke networks may offer adequate diagnostics and treatment. Aim: Aim of this study is to evaluate the accuracy of a novel ED algorithm in differentiating between peripheral and central vestibular causes. Methods: Within the Telemedical Project for Integrative Stroke Care (TEMPiS) a telemedical application including a videooculography (VOG) system was introduced in 2018 in 19 primary care spoke hospitals. An ED triage algorithm was established for all patients with acute dizziness, vertigo or imbalance of unknown cause (ADVIUC) as a leading complaint. In three predefined months all ADVIUC cases were prospectively registered and discharge letters analyzed. Accuracy of the ED triage algorithm in differentiation between central and peripheral vestibular cases was analyzed by comparison of ED diagnoses to final discharge diagnoses. The rate of missed strokes was calculated in relation to all cases with a suitable brain imaging. Acceptance of teleconsultants and physicians in spoke hospitals was assessed by surveys. Results: A total number of 388 ADVIUC cases were collected, with a median of 12 cases per months and hospital (IQR 8-14,5). The most frequent hospital discharge diagnoses are vestibular neuritis (22%), stroke/TIA (18%), benign paroxysmal positioning vertigo (18%) and dizziness due to internal medicine causes (15%). Detection of a central vestibular cause by the ED triage algorithm has a high sensitivity (98.6%), albeit poor specificity (45.9%). One stroke out of 32 verified by brain scan was missed (3.1%). User satisfaction, helpfulness of the project, improvement of care, personal competence and satisfaction about handling of the VOG systems were rated consistently positive. Discussion: The concept shows good acceptance for a telemedical and network-based approach to manage ADVIUC cases in the ED of primary care hospitals. Identification of stroke cases is accurate, while specificity needs further improvement. The concept could be a major step toward a broadly available state of the art diagnostics and therapy for patients with ADVIUC in primary care hospitals.